The thematic dimensions of the term 'information' in the Federal Constitution of the Federative Republic of Brazil of 1988 - Gardini Santos, João Carlos [UNESP]; Chaves Guimarães, José Augusto [UNESP] (My University, 2018)
The term information can be used under different meanings depending on the context and the field it is inserted. More specifically in the Law field, the Brazilian Federal Constitution from 1988 gives special importance to information because it becomes a part of the fundamental rights of the citizens. This paper aims to identify and to analyze the thematic dimensions of the term information in the mentioned Federal Constitution, by means of the application of Bardińs methodology of content analysis and according to subject categories previously established by Santos (2017). It is possible to conclude that although there is a considerably low incidence of the term information, it receives a high specificity in the analyzed document, and is more directly related to the information access ant to the information freedom.
As dimensões temáticas do termo 'informação' na Constituição Federal de 1988 da República Federativa do Brasil
Keywords: Brazil; Constitutions; Content analysis; Fundamental rights; Information; Information access; Information freedom